Apelin Inhibits Angiotensin II-Induced Atrial Fibrosis and Atrial Fibrillation via TGF-β1/Smad2/α-SMA Pathway - Lv, Wenkui; Zhang, Ling; Cheng, Xinchun; Wang, Hongli; Qin, Wen; Zhou, Xianhui; Tang, Baopeng (Frontiers in Physiology, 2020)
Background: Angiotensin II (Ang II) could promote the development of atrial fibrosis in atrial fibrillation (AF). Apelin can inhibit the occurrence of myocardial fibrosis. However, the effect of apelin on Ang II-induced atrial fibrosis and subsequent AF still remains unknown. Objective: In the present study, we examined the effect of apelin on the suppression of atrial fibrosis and subsequent AF, and investigated its underlying mechanisms. Methods: Sprague-Dawly rats were treated for 2 weeks with Ang II (1080 ug/kg/24h) and apelin-13 (140 ug/kg/24h) using implantable mini-pumps. The incidence of AF induced by atrial pacing was determined. Atrial electrophysiological mapping was recorded by a 32-electrode microelectrode array (MEA). Blood was collected to measure the levels of Ang II and apelin. Atrial tissue samples were preserved to assess the pathohistological changes, DDR2 and α-SMA co-staining was performed, and the protein expression of Smad2 phosphorylation was evaluated. Results: Apelin significantly inhibited Ang II-induced atrial fibrosis (HE:1.45±0.11 vs 6.12±0.16, P<0.05; Masson:1.49±0.25 vs 8.15±0.23, P<0.05; Picrosirius Red:1.98±0.64 vs 9.59±0.56, P<0.05, respectively) and decreased the vulnerability of AF (inducibility of AF: z=-4.40, P<0.05; total time of AF episodes: z=-4.349, P<0.05). Left atrial epicardial mapping studies demonstrated preservation of atrial conduction homogeneity by apelin. The protective effects of apelin from fibrotic remodeling were mediated by suppression of Smad2-dependent fibrosis. Conclusions: Apelin potently inhibited Ang II-induced atrial fibrosis and subsequent vulnerability to AF induction via suppression TGF-β/Smad2/α-SMA pathway. Our results indicated that apelin might be an effective up-stream therapy for atrial fibrosis and AF.